Identification of Key Biomarkers in Systemic Lupus Erythematosus by a Multi-Cohort Analysis - Wei, Meilin; Dong, Qiguan; Chen, Shaoqiu; Wang, Junlong; Yang, Hua; Xiong, Qin (Frontiers in Immunology, 2022)
Systemic lupus erythematosus (SLE) is an autoimmune disease that affects multiple body systems with heterogeneous clinical manifestations. Since gene expression analyses have been accomplished on diverse types of samples to specify SLE-related genes, single-cohort transcriptomics have not produced reliable results. Using an integrated multi-cohort analysis framework, we analyzed whole blood or immune cells from SLE patients from three transcriptomics cohorts (n=1222) and identified a five-gene signature distinguishes SLE patients from controls. We validated the diagnostic performance of this five-gene signature in six independent validation cohorts (n= 469), with an area under the receiver operating characteristic curve of 0.88 [95% CI 0.7 − 0.96]. This five-gene signature is significant associated with the proportion of SLE immune cells, and generalizable across ages and sample types with real diagnostic value for clinical application.